2022
DOI: 10.1007/s13300-022-01221-3
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Subcutaneous Semaglutide Versus Empagliflozin in Type 2 Diabetes Uncontrolled on Metformin Alone in Denmark

Abstract: Introduction: International and Danish guidelines recommend the use of glucagon-like peptide 1 receptor agonists (GLP-1 RA) and sodium-glucose cotransporter 2 (SGLT-2) inhibitors already in second line in the management of type 2 diabetes (T2D). The objective of this study was to evaluate the long-term costeffectiveness (CE) of subcutaneous (SC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…However, decisionmakers should also look at long-term cost-effectiveness in prioritizing and decision-making [11]. Our study supports the short-term estimates from Ehlers 2022 [12], but cannot address long-term cost-effectiveness, which remains to be explored in further studies.…”
Section: Comparison With Other Studiesmentioning
confidence: 60%
See 4 more Smart Citations
“…However, decisionmakers should also look at long-term cost-effectiveness in prioritizing and decision-making [11]. Our study supports the short-term estimates from Ehlers 2022 [12], but cannot address long-term cost-effectiveness, which remains to be explored in further studies.…”
Section: Comparison With Other Studiesmentioning
confidence: 60%
“…Few, if any, population-based studies have directly compared observed healthcare costs in new users of empagliflozin vs. new users of a GLP-1RA in a nationwide setting. A recent Danish simulation study used pooled data from clinical trials to evaluate the cost-effectiveness of subcutaneous semaglutide vs. empagliflozin among patients with type 2 diabetes treated with metformin who required treatment intensification [ 12 ]. The study found that the difference in costs between the two groups was mainly driven by different prices of the GLP-1RA and the SGLT2i.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations